The typology of constitutions and the Imposed constitution - Sherzad Ahmed Ameen AL-Najjar; Abdulrahman Hamdi Abdulmajeed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
One of the main challenges that faces any scholar or researcher after defining any legal term is how and why to organise them in different categories. Imposed constitutions as a new term which has lately attracted many researchers tends to be shown as an alien to the classic and traditional types of known constitutions. The main challenge which prompts quickly after hearing this term is if there are imposed constitutions, so what are the un-imposed ones? In This article focuses on finding a place for the imposed constitutions by clarifying that the imposed constitution is a stand-alone type that does not have a counterpart as its name may suggest.